2015
DOI: 10.1111/jai.12961
|View full text |Cite
|
Sign up to set email alerts
|

New data on the longevity of coastal cod Gadus morhua Linnaeus, 1758 in the White Sea

Abstract: Summary The cod, Gadus morhua, is a common and abundant demersal fish in the White Sea coastal zone. The published data on the maximum age of White Sea cod still requires additional documentation, because some authors have noted difficulties in age determination by otoliths of large specimens. To obtain accurate data on the longevity of this species in the White Sea, an image analysis of thin‐sections of otoliths was made for age estimation. Research surveys in the Chupa Inlet and adjacent waters of the Kandal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Cod from the White Sea are unique as they are the only coastal cod population inhabiting the Arctic waters of the North Atlantic. Although its life history is poorly understood, recent studies have suggested it to be resident in the White Sea and spawn under the ice at water temperatures as cold as −1.8°C (Makhotin, 2016; Yershov, Marschal, Ereskovsky, & Vishnyakov, 2016). Earlier, White Sea cod has been ascribed to a subspecies due to its divergent biology ( Gadus morhua marisalbi: Derjugin 1920), and genetic analyses using mtDNA polymorphisms have confirmed its recent divergence from Gadus morhua (Zelenina, Makeenko, Volkov, & Mugue, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cod from the White Sea are unique as they are the only coastal cod population inhabiting the Arctic waters of the North Atlantic. Although its life history is poorly understood, recent studies have suggested it to be resident in the White Sea and spawn under the ice at water temperatures as cold as −1.8°C (Makhotin, 2016; Yershov, Marschal, Ereskovsky, & Vishnyakov, 2016). Earlier, White Sea cod has been ascribed to a subspecies due to its divergent biology ( Gadus morhua marisalbi: Derjugin 1920), and genetic analyses using mtDNA polymorphisms have confirmed its recent divergence from Gadus morhua (Zelenina, Makeenko, Volkov, & Mugue, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…LG12 has previously been found to differentiate between North Sea and coastal cod in the southern Norway (Sodeland et al, 2016). (Makhotin, 2016;Yershov, Marschal, Ereskovsky, & Vishnyakov, 2016). Earlier, White Sea cod has been ascribed to a subspecies due to its divergent biology (Gadus morhua marisalbi:…”
Section: Patterns In Non-neutral Snps and Reconstructed Haplotypesmentioning
confidence: 99%
“…Otoliths are present in various vertebrate taxa, but have been mainly studied in teleosts (e.g. [21,27,28]). Otoliths are calcified structures in the inner ears of teleosts and play a role in equilibration.…”
Section: Growth Bands Countmentioning
confidence: 99%